Characterization of gas-liquid flows in stirred vessels using pressure and torque fluctuations - Khopkar, A. R.; Panaskar, S. S.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2005)
Gas-liquid flows in a stirred vessel exhibit different flow regimes and demonstrate complex interaction of transport processes with varying spatio-temporal scales. The knowledge of key space and time scales of fluid dynamics is important for designing and enhancing the performance of gas-liquid stirred reactor. The present study uses simple, robust, and nonintrusive experimental techniques (torque and pressure sensors) to characterize the fluid dynamics in a gas-liquid stirred vessel. Time series obtained from the pressure and torque sensors were analyzed to develop criteria for flow regime identification. Further analyses of torque and pressure time series were done to extract valuable information of different time scales of fluid dynamics. The detailed analysis of torque and wall pressure fluctuations provided not only an insight into the fluid dynamics but also a possible opportunity to on-line monitoring of gas-liquid flows in stirred vessel.

Computational study of a single-phase flow in packed beds of spheres - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
Packed-bed reactors are widely used in petrochemical, fine chemical, and pharmaceutical industries. Detailed knowledge of interstitial flow in the void space of such packed-bed reactors is essential for understanding the heat and mass transfer characteristics. In this paper, fluid flow through the array of spheres was studied using the unit-cell approach, in which different periodically repeating arrangements of particles such as simple cubical, 1-D rhombohedral, 3-D rhombohedral, and face-centered cubical geometries were considered. Single-phase flow through these geometries was simulated using computational fluid dynamics (CFD). The model was first validated by comparing predicted results with published experimental and computational results. The validated model was further used to study the effect of particle arrangement/orientation on velocity distribution and heat transfer characteristics. The simulated results were also used to understand and to quantify, relative contributions of surface drag and form drag in overall resistance to the flow through packed-bed reactors. The model and the results presented here would be useful in elucidating the role of microscopic flow structure on mixing and other transport processes occurring in packed-bed reactors. (C) 2005 American Institute of Chemical Engineers.
Keywords: CFD; drag; heat transfer; packed bed; packing arrangement

CFD simulation of gas-liquid stirred vessel: VC, S33, and L33 flow regimes - Khopkar, A. R.; Ranade, V. V. (AICHE Journal, 2006)
A comprehensive computational model based on the Eulerian-Eulerian approach was developed to simulate gas-liquid flows in a stirred vessel. A separate submodel was developed to quantitatively understand the influence of turbulence and presence of neighboring bubbles on drag acting on bubbles. This submodel was used to identify an appropriate correlation for estimating the interphase drag force. The standard k-epsilon turbulence model was used to simulate turbulent gas-liquid flows in a stirred vessel. A computational snapshot approach was used to simulate motion of the standard Rushton turbine in a fully baffled vessel. The computational model was mapped onto FLUENT4.5, a commercial CFD solver. The model predictions were compared with the previously published experimental data of Bombac and co-workers. The model was used to simulate three distinct flow regimes in gas-liquid stirred vessels: vortex clinging (VC), alternating small cavities (S33), and alternating large cavities (L33). The predicted results show reasonably good agreement with the experimental data for all three regimes. The computational model and results discussed in this work would be useful for understanding and simulating gas holdup distribution and flow regimes in stirred vessels. (c) 2006 American Institute of Chemical Engineers.
Keywords: computational fluid dynamics (CFD); Flow regimes; gas holdup distribution; Rushton turbine; stirred vessel

CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel

CFD simulation of shortstopping runaway reactions in vessels agitated with impellers and jets - Dakshinamoorthy, D.; Khopkar, A. R.; Louvar, J. F.; Ranade, V. V. (Journal of Loss Prevention in the Process Industries, 2006)
Runaway reactions are continuing to be a problem in the chemical industry. A recent study showed that 26% of our major chemical plant accidents are due to runaways. The consequences of runaway reactions are usually mitigated with (a) reliefs and containment systems or (b) shortstopping (reaction inhibition). This study covers the concept of shortstopping. One of the major reasons for runaways is power failure. In the advent of a power failure, mixing an inhibiting agent with the reactor contents is challenging. However, jets or impellers driven by a small generator can be used for mixing. This study compares shortstopping results in vessels agitated with jets and impellers using computational fluid dynamics (CFD). A commercial CFD code, Fluent is used. For shortstopping systems relying on jet mixing, angle and diameter of jet nozzle and jet velocity are the key design/operating parameters. For the systems with impellers, type, size and RPM of impeller are the key parameters. In this work, mixing with a jet mixer is first investigated for three nozzle diameters and two angles of injection. The best jet mixer configuration on the basis of mixing time is used for shortstopping studies. The simulated shortstopping results with the jet mixer are then compared with those obtained with impeller (Rushton and pitched blade turbine) stirred vessels. Our results identify the conditions for effective shortstopping; i.e., agitation requirements, locations for adding the inhibitor, and the quantity of inhibitor. The distribution of excess inhibitor is shown to be an important and essential design criterion for effective shortstopping when using impeller stirred vessels. The comparative study with a single jet shows that jet mixer is ineffective when used for shortstopping. Efforts such as adding excess inhibitor and inhibition with higher reaction rates at the same power, proved to be ineffective when using jet mixer compared to the results with impellers. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; impeller stirred vessels; jet mixer; runaway reaction; shortstopping

Computational fluid dynamics simulation of the solid suspension in a stirred slurry reactor - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2006)
A comprehensive computational fluid dynamics CFD model was developed in the present study to gain insight into the solid suspension in a stirred slurry reactor. The preliminary simulations highlighted the need for the correct modeling of the interphase drag force. A two-dimensional model problem was then developed using CFD to understand the influence of free stream turbulence on the particle drag coefficient. The proposed correlation was then incorporated in a two-fluid model (Euler-Euler) along with the standard k-epsilon turbulence model with mixture properties to simulate the turbulent solid-liquid flow in a stirred reactor. A multiple reference frame approach was used to simulate the impeller rotation in a fully baffled reactor. A computational model was mapped on to a commercial CFD solver FLUENT6.2 (of Fluent Inc., USA). The model predictions were compared with the published experimental data of Yamazaki et al. [Powder Technol. 1986, 48, 205] and Godfrey and Zhu [AIChE Symp. Ser. 1994, 299, 181]. The predicted results show reasonably good agreement with the experimental data. The computational model and results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.

CFD simulation of gas-liquid flows in a reactor stirred by dual rushton turbines - Kasat, Gopal R.; Pandit, Aniruddha B.; Ranade, V. V. (International Journal of Chemical Reactor Engineering, 2008)
In the present work, we have simulated gas-liquid flows in a tall stirred reactor equipped with dual Rushton turbines. A two fluid model along with the standard k-epsilon turbulence model and modified drag coefficient, (proposed by Khopkar & Ranade, 2006) accounting for the effect of bulk turbulence, was used to simulate the dispersed gas-liquid flow in a stirred reactor. The multiple reference frames (MRF) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc. USA). The model was used to simulate three distinct flow regimes in a gas-liquid stirred reactor: L33-VC (lower impeller-upper impeller), S33-VC and VC-VC. The model predictions were compared with the published experimental data of Bombac & Zun (2000). The predicted results show good agreement with the experimental data for all the three flow regimes. The computational model presented in this work would be useful for simulating different flow regimes in a gas-liquid stirred vessel.
Keywords: computational fluid dynamics; dual Rushton turbine; Flow regimes; gas hold-up distribution; stirred reactor

CFD simulation of liquid-phase mixing in solid-liquid stirred reactor - Kasat, Gopal R.; Khopkar, A. R.; Ranade, V. V.; Pandita, A. B. (Chemical Engineering Science, 2008)
A comprehensive CFD model was developed to gain an insight into solid suspension and its implications on the liquid-phase mixing process in a solid-liquid stirred reactor. The turbulent solid-liquid flow in a stirred reactor was simulated using a two-fluid model with the standard k-epsilon. turbulence model with mixture properties. The multiple reference frames (MRFs) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model with necessary sub-models was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc., USA). The predicted solid concentration distribution was compared with the experimental data of Yamazaki et al. [ 1986. Concentration profiles of solids suspended in a stirred tank. Powder Technology 48, 205-216]. The computational model was then further extended to simulate and understand the implications of the suspension quality on liquid-phase mixing process. The computational model and the predicted results discussed here will be useful for understanding the liquid-phase mixing process in stirred slurry reactors in various stages of solid suspension. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: CFD; mixing; solid suspension; stirred reactor

CFD Simulation of bubble columns: modeling of nonuniform gas distribution at sparger - Rampure, M. R.; Mahajani, S. M.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2009)
Most laboratory bubble columns are equipped with sieve plate spargers. The sieve plate spargers are known to lead to nonuniform gas distribution. It is important to account for such nonuniform gas distribution at the sparger in the computational model before experimental data collected from such columns are used to fit the model parameters. In this article, such an attempt is made. A detailed, 3D CFD model was developed to simulate unsteady gas-liquid flows in bubble Columns with sieve plate spargers. The sensitivity of the nonuniformity of gas distribution at the sparger with sparger resistance was examined. The model predictions were compared with the experimental data. The developed model and presented results will be useful for Simulating industrial bubble columns.

Catalysis and catalytic processes - Ranade, V. V.; Joshi, S. S. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst that provides an alternative route of reaction with lower activation energy and better control of selectivity can make a substantial impact on process viability and economics. In this chapter, the basics of catalysis and catalytic processes are introduced. Some aspects of reaction and reactor engineering required to realize catalytic processes in practice are also discussed. In addition, the organization of the book is outlined.

Catalysis for fine and specialty chemicals - Joshi, S. S.; Bhatnagar, A.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
The fine and specialty chemical industry is extremely diverse, encompassing pharmaceuticals, dyestuffs, food additives, agrochemicals, polymer additives, flavors and fragrances, various chemical intermediates, etc. Fine and specialty chemicals have been around for more than 100 years and they are produced with the aim of either being used as is or in the form of additives/formulations. These organic chemicals are generally manufactured in batch or semibatch processes. Most of these generally involve multistep processes and often generate significant by-products/effluents per kg of useful products. Catalysis can be effectively used to reduce such waste generation and to minimize consumption of raw materials. In this chapter, we present various applications of homogeneous, as well as heterogeneous catalysis and catalytic processes, which are particularly relevant to fine and specialty chemicals

Catalytic reaction engineering - Gunjal, P. R.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
hemical reaction engineering has contributed remarkably in bringing laboratory-developed chemistry into commercial practice. Reaction engineering is useful for analysis of reactions, identifying rate-limiting steps, determining overall rates, selection of reactor configuration and design and scale-up of reactors. Reaction engineering also provides useful insights into catalytic cycles and provides clues for improving catalyst systems. It essentially includes all the activities necessary to evolve best possible hardware and operating protocol for the reactor to carry out the desired transformation of raw materials (or reactants) into value-added products. This chapter provides an overview of reaction engineering aspects of catalytic processes.

Characterizing flow and solid suspension in optimax crystallization workstation - Sardeshpande, M.; Pandit, A.; Vedantam, S.; Ranade, V. V. (North American Mixing Forum 2016 - Core Programming Area at the 2016 AIChE Annual Meeting, 2016)